The relationship between person-job fit, employee engagement and turnover intention: A proposed framework - Koe, Wei Loon; Krishnan, Ramesh; Ahmad, Nur Azreen Farihah; Alias, Nurul Ezaili; Othman, Rozana; Kanchymalay, Kasturi (International Foundation for Research and Development, 2023)
Past studies have identified the existence of a positive relationship between individual employees and their respective jobs as well as current organizations which resulted in more favorable attitudes and behaviors of employees. Although various types of research have been conducted on the person-job fit (P-J fit), few researches that discussed the relationship between P-J fit and turnover intention particularly in identifying the mechanisms that may help to explain these relationships. Thus, this study focuses on outlying the propositions on the potential role of employee engagement as a mediator between P-J fit and one aspect of organizational outcomes (turnover intention). Social Exchange Theory and Job Characteristic theory are adopted in explaining the relationships among the variables. Lastly, suggestions for future studies are proposed.